Analisis Financial Distress Berdasarkan Model Springate, Zmijewski, Dan Grover Pada Perusahaan E-Commerce Di Bursa Efek Indonesia Periode 2021-2023 - Defiyatun Nur Safitri; Eka kurnia Patmasari; Mahfud Nugroho (Jurnal Ekonomika dan Bisnis, 2025)
This study aims to identify and analyze financial distress using the Springate, Zmijewski, and Grover models to predict the bankruptcy of e-commerce companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The research employs a descriptive qualitative approach, utilizing secondary data in the form of financial statements. The results show that based on the Springate model for the 2021–2023 period, there was one company in the safe area and three companies experiencing distress. According to the Zmijewski model, no companies were found to be in distress during the same period. Meanwhile, the Grover model indicated that two companies were in the safe area and two were in distress. The accuracy level of the Springate model was found to be higher than that of the Zmijewski and Grover models, with an accuracy rate of 91.67% and the lowest type of error, namely Type I error at 0% and Type II error at 8.33%. In comparison, the Zmijewski model had an accuracy rate of 25% with Type I error at 0% and Type II error at 75%, while the Grover model had an accuracy rate of 75% with Type I error at 0% and Type II error at 25%.